2021
DOI: 10.3389/feduc.2021.681840
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self-Regulation, Chronotype and Personality in University Students During the Remote Learning Phase due to COVID-19

Abstract: During the COVID-19 shutdown phase in Germany, universities stopped presence teaching and students had to turn to digital instruction. To examine their capability to cope with the changed learning situation, we assessed how basic psychological need satisfaction and frustration, motivational regulation, vitality, and self-efficacy of 228 German biology-teaching students (75% female) relate to their chronotype and personality (Big Five). Specifically, we were interested in possible effects of chronotype and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 89 publications
(134 reference statements)
2
21
0
Order By: Relevance
“…Interestingly, Besser et al (2020) observed an indirect positive effect of extraversion on learning experience through adaptability. Staller et al (2021), however, saw a negative relation between extraversion and intrinsic motivational regulation, while in the other studies, no significant associations between extraversion and learning gain, self-efficacy, or learning satisfaction were found.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, Besser et al (2020) observed an indirect positive effect of extraversion on learning experience through adaptability. Staller et al (2021), however, saw a negative relation between extraversion and intrinsic motivational regulation, while in the other studies, no significant associations between extraversion and learning gain, self-efficacy, or learning satisfaction were found.…”
Section: Resultsmentioning
confidence: 54%
“…As a result, because they are more intrinsically driven, openness to experience may ease the transition and adjustment to the new circumstances (Audet et al, 2021). As demonstrated by Staller et al (2021), openness to experiences yields a positive correlation with self-efficacy. Furthermore, in line with the previous study, it was related to the self-determined types of motivational regulation.…”
Section: Resultsmentioning
confidence: 99%
“…However, even before the Corona Big five personality and Home Study performance -6 -crisis, conscientiousness was found to be related to motivation and satisfaction in online learning and performance (Schniederjans & Kim, 2005;Shih et al, 2013). The motivational self-regulation and selfefficacy of more conscientious students likewise favored better handling of the Home Study situation in the context of pandemic online semesters (Staller et al, 2021).…”
Section: Personality and Home Studymentioning
confidence: 96%
“… Arslan (2021) showed that, for example, loneliness and subjective vitality of college students are negatively correlated. Individuals with certain, relatively stable characteristics like morning-orientation, conscientiousness, openness, and low neuroticism seemed to cope better with the lockdown with respect to outcomes such as vitality, self-determined motivation, and BPNS ( Staller et al, 2021 ).…”
Section: Distance Learning Motivation and Well-beingmentioning
confidence: 99%